2001
DOI: 10.1046/j.1439-037x.2001.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Isotope Discrimination and Grain Yield Variations among Tetraploid Wheat Species Cultivated under Contrasting Precipitation Regimes

Abstract: Nineteen accessions belonging to six tetraploid wheat species were evaluated and compared for carbon isotope discrimination and grain yield during two successive cropping seasons (1995 and 1996) under Mediterranean rainfed conditions. The two seasons differed markedly in precipitation regime. A wide variation for the measured traits was observed among the 19 accessions for carbon isotope discrimination and grain yield in both years. Significant differences were also noted between species accessions for Δ and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
1
14
1
Order By: Relevance
“…The present study indicates that the δ 13 C values are more positive at normal temperature than during nocturnal warming, which is inconsistent with the findings of Su et al (2000). Furthermore, it has been shown that the carbon isotope discrimination (Δ) is positively correlated with the wheat grain yield (Merah et al 2001), which is also inconsistent with the present result, which shows that the sink organ (root) has more positive δ 13 C values. However, Qian et al (2004) reported that the large decrease in δ 13 C of grass is paralleled by limited root growth.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study indicates that the δ 13 C values are more positive at normal temperature than during nocturnal warming, which is inconsistent with the findings of Su et al (2000). Furthermore, it has been shown that the carbon isotope discrimination (Δ) is positively correlated with the wheat grain yield (Merah et al 2001), which is also inconsistent with the present result, which shows that the sink organ (root) has more positive δ 13 C values. However, Qian et al (2004) reported that the large decrease in δ 13 C of grass is paralleled by limited root growth.…”
Section: Discussioncontrasting
confidence: 99%
“…The result of Qian et al (2004) shows that great reduction in δ 13 C of a grass is paralleled with a decrease in root growth. However, Merah et al (2001) reported that the carbon Δ is positively associated with wheat grain (a sink organ) yield, being similar the present results showing an increase both in Δ values and biomass in roots. For the perennial grass Leymus chinensis, higher temperature leads to greater decrease in carbon isotope discrimination in root than in leaf, showing a low adaptation to water stress (Xu and Zhou 2005a).…”
Section: Discussionsupporting
confidence: 92%
“…Along with evolution from diploid to hexaploid (the cultivated common wheat), both yield and quality traits are improved (Merah et al 2001, Chinnusamy and Khanna-Chopra 2003, Xiong et al 2006). The other physiological traits also change during the evolution.…”
Section: Discussionmentioning
confidence: 99%